2009
DOI: 10.1007/s11250-009-9421-9
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro anthelminthic activity of crude aqueous extracts of Aloe ferox, Leonotis leonurus and Elephantorrhiza elephantina against Haemonchus contortus

Abstract: Aloe ferox (Mill), Leonotis leonurus (L) R. BR; and Elephantorrhiza elephantina (Burch.) Skeels are plants frequently used by resource-limited farmers in the Eastern Cape Province to control gastrointestinal parasites in goats. A study was conducted to validate their anthelminthic activities in-vitro on the egg and larvae of the nematode parasite Haemonchus contortus. The crude aqueous extracts of leaves of A. ferox and L. leonurus; and roots of E. elephantina were used. Eggs and larvae of the parasite were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…e most abundant components of the volatile compounds included 3, 6 octatriene (23.86%), 3-cyclohexane-1-hetanol (7.31%), bornylene (5.24%), 1, 3-cyclopentadiene (4.07%), and 5-methyl-3-heptanol (3.92%). Scienti�c studies have veri�ed numerous traditional uses such as laxative effects [30] and antioxidant [31], antiin�ammatory [32,33], antimicrobial [34], anthelmintic [35], and anticancer [36] properties. Using the low-dose streptozotocin diabetes rat model, recent studies have shown promise of A. ferox in treating diabetes [37].…”
Section: Phytochemistry and Biologicalmentioning
confidence: 99%
“…e most abundant components of the volatile compounds included 3, 6 octatriene (23.86%), 3-cyclohexane-1-hetanol (7.31%), bornylene (5.24%), 1, 3-cyclopentadiene (4.07%), and 5-methyl-3-heptanol (3.92%). Scienti�c studies have veri�ed numerous traditional uses such as laxative effects [30] and antioxidant [31], antiin�ammatory [32,33], antimicrobial [34], anthelmintic [35], and anticancer [36] properties. Using the low-dose streptozotocin diabetes rat model, recent studies have shown promise of A. ferox in treating diabetes [37].…”
Section: Phytochemistry and Biologicalmentioning
confidence: 99%
“…One promising alternative has been to research and identify plant products with anthelmintic properties (MAPHOSA et al, 2010). The selection of candidate plants with nematicidal activity involves several experimental stages, including an initial screening using in vitro assays with free-living stages of H. contortus (CAMURÇA-VASCONCELOS et al, 2005), and subsequent in vivo evaluations (JESÚS-GABINO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These concerns have led to the search for and evaluation of alternative control methods (ATHANASIADOU et al, 2001). One promising alternative investigated for the control of gastrointestinal parasites has been the use of phytotherapics (MAPHOSA et al, 2010). Efforts are being made to evaluate several medicinal plants for their anthelmintic potential in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%